2020
DOI: 10.2147/dmso.s280152
|View full text |Cite
|
Sign up to set email alerts
|

<p>Incidence of Diabetic Foot Ulcer and Its Predictors Among Diabetes Mellitus Patients at Felege Hiwot Referral Hospital, Bahir Dar, Northwest Ethiopia: A Retrospective Follow-Up Study</p>

Abstract: The incidence of a diabetic foot ulcer (DFU) is increasing over the previous decade with an increasing prevalence of diabetes mellitus (DM). Despite the increasing incidence of DFU, there is limited information about the problem in Ethiopia. Hence, this study aimed to investigate the incidence of DFU and its predictors among newly diagnosed DM patients who were on follow-up at Felege Hiwot Referral Hospital. Methods: Institution-based retrospective follow-up study was conducted at Felege Hiwot Referral Hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 45 publications
0
24
3
1
Order By: Relevance
“… 6 The lifetime risk of developing foot ulcers among diabetic patients ranges from 19% up to 34%, and about 85% of all diabetic lower limb amputations (DLLA) are preceded by DFUs. 7 , 8 Mortality rate following DLLA because of foot ulcers ranges from 24.6% within 5 years to 45.4% within 10 years. 9 Beside morbidity and mortality, DFUs impose a huge socio-economic burden on the patients and their families.…”
Section: Introductionmentioning
confidence: 99%
“… 6 The lifetime risk of developing foot ulcers among diabetic patients ranges from 19% up to 34%, and about 85% of all diabetic lower limb amputations (DLLA) are preceded by DFUs. 7 , 8 Mortality rate following DLLA because of foot ulcers ranges from 24.6% within 5 years to 45.4% within 10 years. 9 Beside morbidity and mortality, DFUs impose a huge socio-economic burden on the patients and their families.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with diabetes are at increased risk of foot ulcer development and progression. If the risk factors are already present, such as hypertension, cardiovascular disease, peripheral vascular disease and nephropathy or renal failure, then the risk is augmented with non-healing ulcer for a long time and poor prognosis with high morbidity and mortality [31][32][33][34][35][36][37]. Hence, according to our study it is recommended that physician should take detailed history, screening for risk factors, with complete laboratory analysis and management of risk factors simultaneously with best available medications to prevent further diabetes complications.…”
Section: Discussionmentioning
confidence: 88%
“…[4] In a 2017 study in Khartoum the occurrence of DFU was 18.1%. [5] A study of DM patients in Ethiopia [6] showed a relatively high incidence of DFU (4 per 100 person-years). A high body mass index (BMI) was one of the significant predictors, along with nephropathy and retinopathy.…”
Section: Research Articlementioning
confidence: 99%